A large-volume lithium salt, electrolyte and solid-state battery
By using materials such as sulfonimide lithium salt and polymer matrix in lithium-ion battery electrolytes, the problems of low lithium ion migration and insufficient performance of single ion conductive electrolytes are solved, and batteries with high ion conductivity and lithium ion migration are achieved, improving the performance and stability of the battery.
Patent Information
- Application Number
- CN202411909262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The number of lithium ions migration in existing lithium-ion battery electrolytes is low, resulting in polarization of internal concentration of the battery, affecting the battery capacity, working voltage and power. In addition, the single-ion conductive electrolyte has problems with insufficient ion conduction performance, low current density and interface compatibility.
The lithium sulfonimide salt is used as the lithium salt, combined with polymeric matrix, additives and organic solvents, and large-volume lithium salt electrolyte is prepared. By reducing the electrostatic effect of anions and cations and fixing anions, the ion conductivity and lithium ion migration number are improved.
It significantly improves the ion conductivity, lithium ion migration number and thermal stability of lithium ion batteries, enhances the rate performance and high-temperature cycling performance of the battery, and extends the service life of the battery.
Smart Images

Figure CN119742436A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a large-volume lithium salt electrolyte and a solid-state battery thereof. Background Art
[0002] In the field of lithium-ion battery technology, electrolyte is one of the most core components of the battery, and its performance directly affects the conductivity, chemical stability and safety of the battery. Most of the traditional liquid or solid lithium-ion battery electrolytes are dual-ion conductor electrolytes composed of small molecule lithium salts and organic solvents or polymer matrices. These electrolyte systems have a significant problem, that is, the lithium ion migration number is low. This is because during the battery charging and discharging process, the anions and cations generated by the dissociation of small molecule lithium salts will migrate in opposite directions at the same time, acting as carriers, and the mobility of anions is often higher than that of cations (lithium ion migration number is defined as the ratio of lithium ion mobility to the total mobility of anions and cations). This non-electrode reaction-involved anion migration will lead to concentration polarization inside the battery, which will in turn cause battery capacity decay, operating voltage or power reduction. For lithium metal batteries, anion migration may also promote the growth of lithium dendrites, increase the risk of internal short circuits in the battery, and severely limit the scope of application of lithium metal batteries.
[0003] In the development of the next generation of safer electrolytes, single-ion conducting electrolytes are considered a promising research direction due to their stability and high ion transference number. However, insufficient ion conductivity, low current density, interface compatibility issues, and compatibility issues with positive and negative electrode materials in batteries have limited the commercialization of single-ion conducting electrolytes.
[0004] Therefore, improving the ionic conductivity of single-ion conducting electrolytes and developing solid electrolytes with both high ionic conductivity and high ion migration number have become the focus of research in this field. Summary of the invention
[0005] The present invention aims to provide a method for preparing a large-volume lithium salt electrolyte and a solid-state battery, introduce lithium sulfonamide as a lithium salt, effectively reduce the interface impedance between the electrolyte and the positive electrode and the negative electrode, further improve the ionic conductivity, lithium ion migration number and thermal stability, and achieve the rate performance and high-temperature cycle performance of the assembled battery.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A large-volume lithium salt electrolyte and a solid-state battery, wherein the electrolyte comprises a sulfonyl imide lithium salt, a polymer matrix, an additive and an organic solvent.
[0008] Furthermore, the sulfonyl imide lithium salt has a structure shown in formula (I).
[0009]
[0010] Where n = 3, 4, 5, ...
[0011] Furthermore, the mass percentage of the lithium sulfonyl imide is 10%-50%.
[0012] Furthermore, after solidification, the polymer matrix is one or more of polycarbonate, polyethylene oxide, polymethyl acrylate, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl acetate and polyacrylonitrile, any mixture thereof.
[0013] Furthermore, the mass percentage of the polymer matrix is 10%-60%.
[0014] Furthermore, the additive is any mixture of one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, vinylene carbonate, fluorinated vinyl carbonate, vinyl ethylene carbonate, and acrylic nitrile.
[0015] Furthermore, the mass percentage of the additive is 1%-20%.
[0016] Furthermore, the organic solvent is any mixture of one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl acetate, ethyl propionate, sulfolane, dimethyl sulfoxide, tetrahydrofuran, 1,2-dimethoxypropane, and ethylene glycol dimethyl ether.
[0017] Furthermore, the mass percentage of the organic solvent is 15%-80%.
[0018] Furthermore, the preparation of the large-volume lithium salt electrolyte comprises the following steps:
[0019] 1) dissolving the sulfonyl imide lithium salt, the polymer matrix formed by solidification and the additive in an organic solvent respectively, and mixing them evenly to obtain a mixed solution;
[0020] 2) Injecting the mixed solution into the battery cell and allowing it to stand and solidify to obtain the large-volume lithium salt electrolyte.
[0021] Furthermore, the method for uniform mixing in step 1) is stirring at 200-400 rpm for 12-72 hours at 20-40° C., or using ultrasonic mixing.
[0022] Furthermore, the positive electrode material used to assemble the battery is one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary battery materials lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0023] Furthermore, the negative electrode material used for assembling the battery is one or more of the metal materials lithium and sodium; the alloy materials tin-based alloy and aluminum-based alloy; and the inorganic non-metallic materials graphite and silicon carbon.
[0024] By means of the above technical solution, the present invention has the following advantages and beneficial effects:
[0025] (1) The solid electrolyte of the present invention introduces sulfonyl imide lithium salt. The highly delocalized characteristics of the negative charge on the lithium salt anion can reduce the electrostatic interaction between anions and cations, reduce the dissociation energy of the salt and thus improve the ion conductivity; in addition, the anions in the large-volume lithium salt electrolyte are fixed on the oligomeric chain segments and basically will not migrate during the battery charging and discharging process, thereby effectively increasing the lithium ion migration number.
[0026] (2) Lithium sulfonyl imide is added to the electrolyte as a lithium salt to effectively reduce the interfacial impedance between the electrolyte and the positive and negative electrodes, further improving related properties such as ion conductivity. This results in a solid-state battery with both a high lithium ion transfer number (0.85) and ion conductivity (2.6 mS / cm).
[0027] (3) Compared with the current state of the art in which the electrolyte has low ionic conductivity and low lithium ion migration number, the capacity retention rate of the lithium iron phosphate||lithium full battery assembled with the large-volume lithium salt solid electrolyte of the present invention after 300 cycles under high temperature conditions of 60°C is 98.6%, while the capacity retention rate of the conventional dual-ion conductive electrolyte after 300 cycles is only 73.3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The voltage curve of Example 6 at 60°C and 0.5C
[0029] Figure 2 The cycle performance test diagram of Example 6 and Comparative Example 1 at 60°C
[0030] Figure 3 The charge and discharge curve of Example 6 at 60°C
[0031] Figure 4 The rate performance diagram of Example 6 and Comparative Example 1 is shown in FIG. DETAILED DESCRIPTION
[0032] Before describing the specific implementation methods of the present invention in detail, it should be emphasized that the embodiments described below are only for demonstration and are not intended to limit the present invention. These examples are intended to illustrate the technical solution of the present invention and do not mean that the application or use of the present invention is limited to these examples. Any other embodiments obtained by any person skilled in the art according to the teachings of the present invention without creative work should also be regarded as part of the protection scope of the present invention.
[0033] The specific numerical values mentioned in these embodiments do not represent limitations of the present invention unless otherwise specified. Techniques or methods known to those skilled in the art may not be discussed in detail here, but where appropriate, these techniques and methods should be considered as part of this specification. In all examples, unless otherwise specified, all units of weight are parts by weight, and all percentages are weight percentages. For experimental methods that do not specify conditions, they are usually measured in accordance with national standards; if there are no corresponding national standards, they are carried out in accordance with general international standards or standards proposed by relevant companies.
[0034] Example 1
[0035] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=3), vinyl ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=3) is 15%;
[0036] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0037] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0038] Example 2
[0039] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=4), vinyl ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=5) is 15%;
[0040] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0041] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0042] Example 3
[0043] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=5), ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=5) is 15%;
[0044] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0045] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0046] Example 4
[0047] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=6), vinyl ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=6) is 15%;
[0048] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0049] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0050] Example 5
[0051] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=5), vinyl ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=5) is 20%;
[0052] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0053] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0054] Example 6
[0055] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=5), ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=5) is 30%;
[0056] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0057] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0058] Example 7
[0059] Step 1: In a glove box filled with argon, at room temperature, lithium sulfonimide salt (n=5), vinyl ethylene carbonate, and ethylene oxide are added to dimethyl carbonate respectively, and stirred at 60° C. to obtain a mixed electrolyte; the mass percentage of lithium sulfonimide salt (n=5) is 40%;
[0060] Step 2: Inject the electrolyte into the battery cell and let it stand to solidify;
[0061] Step 3: The electrolyte film obtained in step 2 is used to assemble a LiFePO4||Li full battery, and the battery's AC impedance spectrum, charge and discharge cycle performance at 3.0-4.2V and 0.5C rate at 60°C, and lithium ion migration number are tested.
[0062] Comparative Example 1
[0063] The operation steps are the same as those in Example 1, except that the lithium salt is lithium hexafluorophosphate.
[0064] Comparative Example 2
[0065] The operation steps are the same as those in Example 1, except that the lithium salt is lithium bis(trifluoromethanesulfonyl imide).
[0066] The AC impedance spectra of Examples 1-7 and Comparative Examples 1-2 were measured, and the charge current was measured at 60°C, 3.0-4.2V, and 0.5C rate.
[0067] Tests such as discharge cycle performance and lithium ion migration number.
[0068] AC impedance spectrum test: The single-ion lithium salt electrolyte membrane is sandwiched between two stainless steel blocking electrodes with known surface areas, and tested with an electrochemical workstation at 25°C, with a test frequency range of 100KHz-10mHz and a perturbation voltage of 100mV. The conductivity σ of the electrolyte membrane is calculated by the formula σ=L / ARb, where L is the thickness of the membrane and A is the contact area between the electrolyte membrane and the electrode.
[0069] 60℃ cycle performance test: In a 60℃ environment, the cycle performance of charge and discharge is tested at 3.0-4.2V and 0.5C rate, and the capacity retention rate is recorded after 300 cycles.
[0070] Rate performance test: Under constant current and constant voltage, charge and discharge tests were performed at 0.5C, 1C, 2C, 3C, and 5C, and the discharge specific capacity was recorded.
[0071] Table 1 Performance test results of Examples 1-7 and Comparative Examples 1-2.
[0072]
[0073] From the results in Table 1, it can be seen that the lithium iron phosphate battery constructed with a large-volume lithium salt solid electrolyte based on sulfonamide lithium salt in Examples 1-7 has a capacity retention rate of 98.6% after 300 cycles under 60°C high temperature conditions, showing good thermal stability and cycle stability; while the capacity retention rate of the conventional dual-ion conductive electrolyte of Comparative Examples 1-2 after 300 cycles is only 73.3%, which is significantly lower than the test results of the single-ion conductive electrolyte. The large-volume lithium salt electrolyte and solid-state battery prepared with lithium sulfonamide as the lithium salt exhibit superior performance with both high lithium ion migration number (0.85) and ionic conductivity (2.6mS / cm). In addition, the discharge specific capacity of the electrolyte decreases with increasing current density. Compared with the battery constructed with conventional dual-ion conductive electrolytes, the large-volume lithium salt electrolyte and solid-state battery provided by the present invention can show better performance at different current densities, indicating that the electrolyte can effectively enhance the rate performance of the lithium battery.
[0074] In summary, the large-volume lithium salt electrolyte of the present invention has both high ionic conductivity and lithium ion migration number, which can not only improve the rate cycling performance of lithium batteries, but also inhibit lithium dendrites and enhance the safety of lithium batteries; in addition, the lithium iron phosphate battery assembled with the electrolyte can achieve good cycling performance under high temperature conditions, showing that the electrolyte has excellent thermal stability.
[0075] The description of the above embodiments is intended to illustrate the technical solutions and features of the present invention so that those familiar with the technical field can understand and implement the present invention. These examples do not constitute a limitation on the protection scope of the present invention. Any equivalent changes or improvements made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A large-volume lithium salt, electrolyte and solid-state battery, characterized in that: The electrolyte comprises lithium sulfonyl imide of a structure shown in formula (I), a polymer matrix, additives and an organic solvent. Where n = 3, 4, 5, ...
2. The bulk lithium salt electrolyte according to claim 1, characterized in that The mass percentage of the lithium sulfonyl imide is 10%-50%.
3. The bulk lithium salt electrolyte according to claim 1, characterized in that After solidification, the polymer matrix is one or more of polycarbonate, polyethylene oxide, polymethyl acrylate, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl acetate and polyacrylonitrile, which are mixed at random.
4. The bulk lithium salt electrolyte according to claim 1, characterized in that The mass percentage of the polymer matrix is 10%-60%.
5. The bulk lithium salt electrolyte according to claim 1, characterized in that The additive is any mixture of one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, vinylene carbonate, fluorinated vinyl carbonate, vinyl ethylene carbonate and acrylic nitrile.
6. The bulk lithium salt electrolyte according to claim 1, characterized in that The mass percentage of the additive is 1%-20%.
7. The bulk lithium salt electrolyte according to claim 1, characterized in that The organic solvent is any mixture of one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl acetate, ethyl propionate, sulfolane, dimethyl sulfoxide, tetrahydrofuran, 1,2-dimethoxypropane and ethylene glycol dimethyl ether.
8. The bulk lithium salt electrolyte according to claim 1, characterized in that The mass percentage of the organic solvent is 15%-80%.
9. The bulk lithium salt electrolyte according to claim 1, characterized in that The preparation of the bulk lithium salt electrolyte comprises the following steps: 1) dissolving the sulfonyl imide lithium salt, the polymer matrix formed by solidification and the additive in an organic solvent respectively, and mixing them evenly to obtain a mixed solution; 2) Injecting the mixed solution into the battery cell and allowing it to stand and solidify to obtain the large-volume lithium salt electrolyte.
10. The method for preparing a large-volume lithium salt electrolyte according to claim 6, characterized in that: The method for uniform mixing in step 1) is to stir at 200-400 rpm for 12-72 hours at 20-40° C., or to use ultrasonic mixing.
11. The large-volume lithium salt electrolyte and solid-state battery according to claim 1, characterized in that: The positive electrode material used to assemble the battery is one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary battery materials lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
12. The large-volume lithium salt electrolyte and solid-state battery according to claim 1, characterized in that: The negative electrode material used for assembling the battery is one or more of the metal materials lithium and sodium; the alloy materials tin-based alloy and aluminum-based alloy; the inorganic non-metallic materials graphite and silicon carbon.